Обрив ланцюгiв у реакцiї окиснення органiчних сполук фулереном C60 - Ковтун, Г.О.; Жила, Р.С.; Каменєва, Т.М. (Видавничий дім "Академперіодика" НАН України, 2007)
It is shown that fullerene C60 breaks the сhains of oxidation reactions of organic сompounds (primary and secondary alcohols, styrene, ethylbenzene) by interacting with alkyl and peroxyl radicals (at 50–75 ◦